Party politics and the power to report: informational efficiency in bicameralism - Finke, Daniel; Han, JeongHun (Journal of European public policy, 2014)
The system of single rapporteurships was introduced at times when the European Parliament was trying hard to establish its powers vis-à-vis the Council of Ministers. Over the years, party politics has become increasingly important for European Union legislation. This historical development triggers the question to what extent the powers of the rapporteur depend on her partisan ties to the Council of Ministers. In order to answer this question we analyse legislative reports authored between 2004 and 2009. We argue that the rapporteur can successfully form coalitions inside the European Parliament. However, if the rapporteur's party is represented inside the Council of Ministers, she may be suspected of supporting national rather than partisan interests. Therefore, representation in the Council is a double-edged sword: rapporteurs whose parties are in government find it easier to gain information on the proceedings inside the Council, but they lose credibility with their partisan peers inside the European Parliament.